2003
DOI: 10.1038/sj.ejcn.1601637
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal handling of glycosyl [13C]ureides

Abstract: Objectives: Lactose [ 13 C]ureide has been proposed as a noninvasive marker for oro-caecal transit time in adults and children. The present study investigates the handling of lactose [ 13 C]ureide ( 13 C LU) and glucose [ 13 C]ureide ( 13 C GU) by the gastrointestinal tract and describes the metabolic fates of these substrates and describes the extent of tracer excretion by different routes. Study Design and Subjects: Four subjects underwent five studies in which they ingested a test meal plus (1) no substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 31 publications
1
29
0
Order By: Relevance
“…In the last decade, breath tests with 13 C-labelled glycosyl ureides for measuring the OCTT have been established worldwide (Heine et al, 1995;Ruemmele et al, 1997;Wutzke et al, 1997;Morrison et al, 1998Morrison et al, , 1999Morrison et al, , 2003Geypens et al, 1999;Jackson et al, 1999;van den Driessche et al, 2000;Christian et al, 2002). Furthermore, 15 N-labelled LU has been used for studying colonic nitrogen metabolism as a biomarker to assess the effects of pro-and pre-biotics on the intestinal flora in humans, and for measuring the transfer of 15 N (de Preter et al, 2004;Jackson et al, 2004;Geboes et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, breath tests with 13 C-labelled glycosyl ureides for measuring the OCTT have been established worldwide (Heine et al, 1995;Ruemmele et al, 1997;Wutzke et al, 1997;Morrison et al, 1998Morrison et al, , 1999Morrison et al, , 2003Geypens et al, 1999;Jackson et al, 1999;van den Driessche et al, 2000;Christian et al, 2002). Furthermore, 15 N-labelled LU has been used for studying colonic nitrogen metabolism as a biomarker to assess the effects of pro-and pre-biotics on the intestinal flora in humans, and for measuring the transfer of 15 N (de Preter et al, 2004;Jackson et al, 2004;Geboes et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to several papers published earlier dealing with the evaluation of OCTTs, a reduced and cheaper pre-dosing protocol with merely 5 Â 100 mg LU has been applied in this study. Higher dosages of up to 5 Â 1 g LU have been used in adults so far (Morrison et al, 2003;Wutzke and Glasenapp, 2004). It could be demonstrated that the application of 500 mg 13 C-LU and the pre-dosing with 5 Â 100 mg LU are high enough to induce the enzyme activity and to give reliable results.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it could be demonstrated that pre-dosing with merely 3 Â 120 mg GU as well as the equimolar dosage of 3 Â 200 mg CU is high enough to induce the enzyme activity and to give reliable results. In previously published papers, higher dosages of up to 5 Â 1 g LU have been used in adults (Morrison et al, 2003;Wutzke and Glasenapp, 2004). The relatively low dosage of GU and CU, respectively, applied in this study minimize a potential influence of pre-dosing on OCTT.…”
Section: Discussionmentioning
confidence: 99%
“…Since the primary publication in 1995, 13 CO 2 -breath tests for measuring the OCTT preferentially by using 13 C-LU have become generally accepted worldwide (Heine et al, 1995;Ruemmele et al, 1997;Geypens et al, 1999;Jackson et al, 1999;Van den Driessche et al, 2000;Christian et al, 2002;Morrison et al, 1998Morrison et al, , 1999Morrison et al, , 2003Wutzke and Sattinger, 2006;Schneider et al, 2007;Berthold et al, 2009). It is commonly assumed that 13 C-GU and the corresponding glucose ureide hydrolase are the key substance and the key enzyme, respectively, of the enzymatic sugar ureide degradation process that is exclusively initiated by C. innocuum in the human caecum (Mohr et al, 1999;Wutzke and Glasenapp, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation